Intrinsically disordered amphiphilic peptides as potential targets in drug delivery vehicles. Issue 11 (13th November 2015) - Vincenzi, Marian; Accardo, Antonella; Costantini, Susan; Scala, Stefania; Portella, Luigi; Trotta, Annamaria; Ronga, Luisa; Guillon, Jean; Leone, Marilisa; Colonna, Giovanni; Rossi, Filomena; Tesauro, Diego
<x xml:space="preserve">Abstract</x> Intrinsically disordered proteins/peptides play a crucial role in many physiological and pathological events and may assume a precise conformation upon binding to a specific target.